The physics of warm nuclei with analogies to mesoscopic systems - Hofmann, Helmut, 1941- (Oxford : Oxford University Press, 2008)
The text describes in detail modern developments in theories of small many body systems like nuclear complexes in accelerator experiments or metal clusters.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Nuclear physics; Mesoscopic phenomena (Physics)